KEEFEKTIFAN PEMBELAJARAN MENULIS CERPEN DENGAN MODEL SINEKTIK DAN PETA KONSEP (CONCEPT MAPPING) BERBASIS PEMANFAATAN GENERATIVE AI PADA PESERTA DIDIK KELAS VIII SMP NEGERI 1 SEMARANG - Fitriana, Zidna; Zuliyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of synectics learning model and concept mapping model integrated with the use of Generative Artificial Intelligence (AI) in improving students’ short story writing skills. The background of this study is the low ability of students in generating ideas, developing plots, and organizing narrative structures. This research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The sample consisted of 63 eighth-grade students of SMP Negeri 1 Semarang, divided into two groups: the synectics class (31 students) and the concept mapping class (32 students). Data were collected through pretest and posttest of short story writing and analyzed using descriptive statistics, N-Gain, and independent sample t-test. The results showed that both learning models improved students’ writing skills, as indicated by the increase in mean scores from pretest to posttest. The N-Gain score of the concept mapping class (32.80) was higher than that of the synectics class (20.55), although both were categorized as less effective. The hypothesis testing result showed no significant difference between the two models (Sig. = 0.976 > 0.05), indicating that both models have relatively equal effectiveness. Therefore, it can be concluded that synectics and concept mapping models supported by AI have the potential to improve short story writing skills, but their effectiveness is not significantly different.